IMPLEMENTATION OF LEARNING BASED ON E-WORKSHEETS WITH A SCIENTIFIC APPROACH ON THE MATERIAL OF THE DIGESTIVE SYSTEM IN CLASS XI SMA UNGGULAN AL-MANAR - Gultom, Endang Sulistyarini; Yenda, Azura Nur (Jurnal Pelita Pendidikan, 2025)
This study aims to determine the application of e-worksheet with a scientific approach in class XI IPA SMA Unggulan Al-Manar in the learning process as measured by students' critical thinking skills. The instrument for measuring the question is administered both before and after the implementation of the learning. The data analysis technique employs quantitative analysis, specifically the calculation of the average value, to assess the students' critical thinking skills. The results of the data analysis indicate that the implementation of learning using e-worksheet with a scientific approach can enhance the critical thinking skills of students in class XI IPA at SMA Unggulan Al-Manar. This is evidenced by the change in the cognitive value of students during the pretest and posttest, which fell within the very good category. The average value of students during the pretest was 54.13, while the average value increased to 86.75 during the posttest, indicating an improvement in critical thinking skills.